2019
DOI: 10.1021/jacs.8b09917
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of MnO2 Crystal Structure on Aerobic Oxidation of 5-Hydroxymethylfurfural to 2,5-Furandicarboxylic Acid

Abstract: Aerobic oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA) as a bioplastics monomer is efficiently promoted by a simple system based on a nonprecious-metal catalyst of MnO2 and NaHCO3. Kinetic studies indicate that the oxidation of 5-formyl-2-furancarboxylic acid (FFCA) to FDCA is the slowest step for the aerobic oxidation of HMF to FDCA over activated MnO2. We demonstrate through combined computational and experimental studies that HMF oxidation to FDCA is largely dependent on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
293
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(326 citation statements)
references
References 113 publications
15
293
0
Order By: Relevance
“…The spin‐orbit splitting value of 11.8 eV was estimated from the Figure a, which was very close to the value of Mn 2 O 3 . The asymmetrical Mn 2p 3/2 peaks at 641.8 eV can be deconvoluted into several sub‐peaks with binding energies of 640.8, 641.6, 642.8, and 644.8 eV, which were assigned to Mn 2+ , Mn 3+ , Mn 4+ , and shake‐up peaks, respectively . The relative intensities of Mn 2+ /Mn 4+ and Mn 3+ /Mn 4+ were 0.36 and 0.77, respectively, indicating the existence of relative high proportion of Mn 4+ and potential redox recycle of Mn cations.…”
Section: Resultsmentioning
confidence: 99%
“…The spin‐orbit splitting value of 11.8 eV was estimated from the Figure a, which was very close to the value of Mn 2 O 3 . The asymmetrical Mn 2p 3/2 peaks at 641.8 eV can be deconvoluted into several sub‐peaks with binding energies of 640.8, 641.6, 642.8, and 644.8 eV, which were assigned to Mn 2+ , Mn 3+ , Mn 4+ , and shake‐up peaks, respectively . The relative intensities of Mn 2+ /Mn 4+ and Mn 3+ /Mn 4+ were 0.36 and 0.77, respectively, indicating the existence of relative high proportion of Mn 4+ and potential redox recycle of Mn cations.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, catalytic behaviors linked to the morphology and phase/surface structure of catalysts have been intensively investigated for aqueous electrolyte systems like fuel cells, as well as metal–oxygen batteries . As for MnO 2 polymorphs, the structure‐induced activities are well documented for their electrochemical reaction, and gas‐ and liquid‐phase reactions, which correlated their activities with chemical states of Mn or O, active sites, electron/mass transfer on different phase structure . Additionally, Jin et al very recently reported that a synergistic change of structural disorder inducing the changed surface electron density of layered δ‐MnO 2 can improve aqueous OER and non‐aqueous ORR/OER performance…”
Section: Introductionmentioning
confidence: 99%
“…Thus, developing a new method that utilizes inexpensive catalysts and work under ambient conditions attracts more and more attention. Now, researchers successfully found that the electrochemical oxidation of 5‐HMF was an advantageous method due to its environmentally benign, using water as the oxygen source, and proceeding at ambient temperatures/pressures . Then, Chadderdon et al and Choi et al reported the Au and Pt based catalysts for electrocatalytic oxidation of 5‐HMF to 2,5‐FDCA.…”
Section: Figurementioning
confidence: 99%